Planning Today for Tomorrow’s Research: Analysis of Factors Influencing Participation in a Pediatric Cancer Research Biorepository - Labib, Rania M.; Hassanain, Omneya; Alaa, Maram; Ahmed, Safaa; Abou El-Naga, Sherif (Frontiers in Oncology, 2018)
Background Biobanks have become a powerful tool that fosters biomedical research. The success of biobanks depends upon people’s perception and willingness to donate their samples for research. This is the first biorepository in Egypt, hence, little is known about the beliefs and attitudes of parents toward participation. Aim To investigate the level of willingness of Egyptians to donate samples of their children and themselves for research and the different factors influencing participation. Materials and methods A structured questionnaire was designed covering multiple items expected to affect the enrollment decision. This was conducted in-person, and data collected included demographic data, socioeconomic, and educational level. In addition, in the case of refusal, participants were asked about reasons behind their decision. Results Only about 3.1% of patients have not been enrolled in the project, and 0.3% have withdrawn. Three demographic factors were found having disparate trends in the decision-making process to participate or not: father’s education (p = 0.0001), mother’s education (p = 0.0001), and father’s age (p = 0.034). Conclusion Egyptian parents were willing to donate their samples as well as their children’s samples in our research biorepository. The idea of participation was presented in an interview during which the consent form was explained in a comprehensive transparent way allowing participants the right to refuse or withdraw at any time. Still, different communication approaches are needed with older, more highly educated parents to encourage them to participate.